Analisis Kepuasan Pelanggan Menggunakan Mix Method (Studi Kasus pada Lettice Clinic Tanjung Pinang) - Sukarnadi, Natalia; Raharjo, Susilo Toto (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2019)
This research conducted to analyzed Lettice Clinic’s patient satisfaction index at Tanjung Pinang. Lettice Clinic is a beauty clinic that gives treatment services contains pharmacy installation and beauty skin treatment and also beauty natural like eyelash extention, filler, brow tatoo, etc.This reseach used mix method, first method using IPA (importance performance analysis) quantitative analysis conducted on 100 samples who visit Lettice Clinic and second method is conducted by interview to 3 Lettice Clinic’s Informan. Data was collected by questionary and qualitative research manuscript.The finding through mix method research are Quadrant I (main priority) consist of services attribute employee existing; fast, ontime and clear treatment; and problem solving. Quadrant II (achievement surviving) consist of service attribute physical facility, complaint handling, accuracy and in-depth explaining ability. Quadrant III (Low Priority) consist of service attribute employee readiness, client understanding ability and able to self-placement. Quadrant IV (Too Much) consist of service attribute employee appearance that too good look, too accurate information giving, too fast responses, accuracy command and client treatment. While in-depth interview result showed generally consistent with IPA analysis result.